Effects of microwave treatment of durum wheat kernels on quality characteristics of flour and pasta. (15th June 2019) - Padalino, Lucia; Del Nobile, Matteo Alessandro; la Gatta, Barbara; Rutigliano, Mariacinzia; Di Luccia, Aldo; Conte, Amalia
Highlights: The microwave treatment caused protein denaturation in treated samples. The microwave treatment affected the polymeric protein arrangement. The microwave treatment greatly affected pasting characteristics of wheat flour. The microwave treatment compromised sensory acceptability of pasta. Abstract: The influence of microwave treatment of hydrated durum wheat kernels of two different cultivars ( cv Aureo and Sfinge), on wholemeal flour and pasta quality was addressed. Size exclusion-HPLC and electrophoresis analysis were used to investigate changes in the gluten network arrangement as affected by the microwave treatment. Rheological properties of dough, cooking quality and sensory properties of pasta were also assessed. Results suggested that the microwave treatment on hydrated durum wheat kernels blocks gluten protein conformation through SS bonds formation and the free -SH are no longer able to create a strong network during pasta processing, due to the conformational changes. Rheological study of dough confirmed that the modifications induced by microwave treatment greatly affected pasta making characteristics of wheat flour, with significant negative consequences on product quality, especially for pasta cooking quality. Pasta from treated durum wheat showed low sensory quality, mainly due to high bulkiness and adhesiveness.